2020
DOI: 10.1111/tid.13427
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 clinical manifestations and treatment strategies among solid‐organ recipients: A systematic review of cases

Abstract: Background COVID‐19 has been spreading worldwide with a significant death toll. Solid‐organ transplantation (SOT) recipients are at higher risk due to their suppressed immune system. In this study, we aimed to conduct a systematic review on COVID‐19 clinical manifestations and treatment strategies in SOT recipients. Methods We searched three databases for relevant terms related to COVID‐19 and transplantation. 50 studies, including 337 patients, were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 79 publications
3
21
0
2
Order By: Relevance
“…The presentation of SOT recipients with COVID‐19 appears similar to the general population. Fever (61–83%), cough (45–75%), and diarrhea (22–57%) were the most common symptoms reported 14‐16,71,75,79,80,83‐88 . Abnormalities in chest imaging occurred frequently; cohorts of SOT recipients in New York City reported abnormal chest radiographs in 96%–100% 83,84 .…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation of SOT recipients with COVID‐19 appears similar to the general population. Fever (61–83%), cough (45–75%), and diarrhea (22–57%) were the most common symptoms reported 14‐16,71,75,79,80,83‐88 . Abnormalities in chest imaging occurred frequently; cohorts of SOT recipients in New York City reported abnormal chest radiographs in 96%–100% 83,84 .…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
“…All‐cause mortality during the study period of the UK registry reached 26% for SOT recipients and 10% for those on the waitlist, although local utilization decisions related to resource availability may have impacted these numbers 74 . The largest cohort to date including 482 SOT recipients from more than 50 transplant centers reported 20.5% mortality, and two compilations of cases found 18%–19% mortality overall 17,87,88 . In a UK database analyzing 10926 COVID‐19 related deaths, SOT recipients had a hazard ratio of 3.53 [95% CI 2.77–4.49] for death as compared to the general population 105 .…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
“…A recently published article argued that the use of calcineurin inhibitors would be beneficial in the pandemic course [ 8 ]. Studies have shown that the cytopathic effect of the virus, oxidant system activation, and cytokine storm are cornerstones in the pathogenesis of COVID-19 [ 2 , 3 ]. In the early stages of the COVID-19 pandemic, it was speculated that immunosuppressive therapy would facilitate the cytopathic effects of the virus.…”
Section: Pharmacological Action Of Cnis and Mtori Related To Covid-19mentioning
confidence: 99%
“…In a systematic review including 50 studies and 337 patients, Moosavi et al analyzed the drug modification strategies. Generally, anti-metabolite and CNI were reduced or discontinued, and steroid doses were increased, in patients with solid-organ transplantation and COVID-19 [ 3 ], but patient outcomes could not be assessed if they were associated with decreased immunosuppression or increased steroid dose. There are different strategies determined according to the patient’s clinical condition and the approach of the transplantation centers.…”
Section: Introductionmentioning
confidence: 99%
“…riñón, hígado, pulmón) son similares a los de la población general, aunque presentan con mayor frecuencia síntomas gastrointestinales. En estos individuos la COVID-19 parece ser más grave y tiene una mayor mortalidad (18.4%) en comparación con la población general (Moosavi et al, 2020).…”
Section: Covid-19 Y Trasplante De óRgano Sólidounclassified